2013
DOI: 10.1155/2013/858294
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A2 Lowered by Iron Deficiency and α-Thalassemia: Should Screening Recommendation for β-Thalassemia Change?

Abstract: Screening for β-thalassemia trait (BTT) relies on measuring hemoglobin (Hb) A2. Since multiple factors can affect HbA2 levels, the screening can become unreliable. In 1356 healthy Arabs enrolled into a federally funded premarital BTT screening program, the effects of iron deficiency (ID), α +-thalassemia trait, gender, smoking, and tribalism on HbA2 were studied. The complete blood count and hemoglobin fractions were determined on the entire cohort; serum ferritin (<15 μg/L) in 391 subjects was used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
1
38
0
2
Order By: Relevance
“…No difference was found in MCV and HbA2 levels between the male and female groups (p>0.05). Denic et al 17 reported that HbA2 is not influenced by gender, smoking or tribal allegiance, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…No difference was found in MCV and HbA2 levels between the male and female groups (p>0.05). Denic et al 17 reported that HbA2 is not influenced by gender, smoking or tribal allegiance, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 94%
“…We found that HbA2 levels were significantly decreased in both α +Het , β and α +Hom , β in comparison with simple β carriers (p=0.004 and 0.002, respectively) (table 3). Other studies showed that inheritance of β- and α-thalassaemia mutations in a double heterozygous state decreases or normalises the levels of HbA2 17 18. This is in agreement with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…HbA2 value of 3.3% to 3.8% was considered as borderline and a cut-off of over 3.9% was taken for diagnosis of β-thalassemia trait. [4,[7][8][9] In very few cases, which were not interpreted by HPLC, were confi rmed by amplifi cation refractory mutation system, polymerase chain reaction (PCR-ARMS) technique. [10] …”
Section: Methodsmentioning
confidence: 99%
“…Total Hb levels differ between males and females, and free Hb levels fluctuate depending on the presence of hemolytic conditions, such as infections. On the other hand, sex, race, and infections do not influence HbA2 levels 16,17. Therefore, measuring HbA2 levels would give reliable results pertinent to its involvement in chronic diseases, somewhat analogous to the benefits of HbA1C determination in diabetes, which allows determining the glucose balance for a long period rather than cross-sectional.…”
Section: Discussionmentioning
confidence: 99%